tg(45+x)-3tgx=2

Simple and best practice solution for tg(45+x)-3tgx=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for tg(45+x)-3tgx=2 equation:


Simplifying
tg(45 + x) + -3tgx = 2
(45 * gt + x * gt) + -3tgx = 2
(45gt + gtx) + -3tgx = 2

Combine like terms: gtx + -3gtx = -2gtx
45gt + -2gtx = 2

Solving
45gt + -2gtx = 2

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Reorder the terms:
-2 + 45gt + -2gtx = 2 + -2

Combine like terms: 2 + -2 = 0
-2 + 45gt + -2gtx = 0

The solution to this equation could not be determined.

See similar equations:

| 4m^2+20m=24 | | 2(6+3r)-10= | | tg(45+x)tg(45+x)-3tgx=2 | | ax+cy=c | | -8y=-7x+20 | | (1/6x-1/3) | | 10(-5x-14)=410 | | 3x(5x-5)-4x= | | 23x+5y-33=180 | | 15+6(4+f)-3f=48 | | M-18.95=7.05 | | x-(x*0.2)=85 | | 2.2x^2-1.6x+8=1.6x^2+2.2x+9 | | 4x-y+x+y=8+22 | | -3x-(-5)=-2 | | A=1200(1+0.15*2) | | 1/x=0.28 | | w^2=78 | | -1k= | | (14y-4)+(3x+11)+(x+21)=180 | | 4x+2x+3x=279 | | .75(.25x+8)-(.5x+2)=.23(4-x)-.25 | | c^2=64/25 | | 187=19+7(13+p) | | -8=4q-20+2q | | -27x-1=4 | | (-8p+7)-(2p-4)= | | 540-3x-100=17 | | -c/3-5=17 | | 4p+2p-1=30+7 | | 7+2x=50 | | 14=2y+1 |

Equations solver categories